تطوير مادة التراكيب العربية على أساس التعلم التعاوني لطلبة المدرسة الثانوية الإسلامية الحكومية الثانية بيما - Istaqam, Nur; Hamid, M Abdul (Lugawiyyat, 2019)
This study aims to: (1) Produce Tarākīb teaching materials with the cooperative learning principle for students of  MAN 2 Bima, (2) Find out the effectiveness of Tarākīb teaching materials with cooperative learning principle in MAN 2 Bima. This research is important to do because many students have difficulties in understanding the material of Tarākīb, so by the existence of the Tarākīb teaching materials with cooperative learning principle, it helps students to understand Tarākīb material easier and increase students' interest in learning Tarākīb.The research method used by researcher is research and development, the researcher followed the ten steps of the Borg and Gall model of research and development. Data collection methods used in this study were interview, questionnaire and test. The data obtained were analyzed with qualitative and quantitative approaches. The formula used to test the effectiveness of teaching materials is T-test.The results of this research and development are: (1) The availability of Tarākīb teaching materials. Teaching materials developed by researcher have characteristics and advantages that other books do not have, Tarākīb teaching materials presented with cooperative learning principle, where each chapter is presented with different cooperative learning methods. The first chapter is presented by the student team achievement division method, the second chapter is presented with the teams games tournament method, and the third chapter is presented with the heads numbered method. In addition, Tarākīb teaching materials provide forms of Tarākīb training with various questions, (2) Tarākīb teaching materials with cooperative learning principle was effective to use for students of  MAN 2 Bima by looking at the result of the T-test which is 3,947 of T-table with the significance is 5% of 1,678.